2023
DOI: 10.3390/nu15234915
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting on Neurologic Diseases: Potential Role of Gut Microbiota

Mingke Guo,
Xuan Wang,
Yujuan Li
et al.

Abstract: As the global population ages, the prevalence of neurodegenerative diseases is surging. These disorders have a multifaceted pathogenesis, entwined with genetic and environmental factors. Emerging research underscores the profound influence of diet on the development and progression of health conditions. Intermittent fasting (IF), a dietary pattern that is increasingly embraced and recommended, has demonstrated potential in improving neurophysiological functions and mitigating pathological injuries with few adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 208 publications
0
2
0
Order By: Relevance
“…Recently, IF has emerged as a multifaceted approach that influences long-chain fatty acid oxidation through the intricate interplay of gut microbiota changes and BDNF production [67][68][69]. This triad not only offers insights into the metabolic benefits of IF but also sheds light on the complex connections between the gut, the brain, and metabolic health.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, IF has emerged as a multifaceted approach that influences long-chain fatty acid oxidation through the intricate interplay of gut microbiota changes and BDNF production [67][68][69]. This triad not only offers insights into the metabolic benefits of IF but also sheds light on the complex connections between the gut, the brain, and metabolic health.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of fasting and ketogenic diets have been demonstrated in several studies in mouse models of EAE by altering the gut microbiota of MS patients through dietary habits ( Bai et al, 2021 ; Brenton et al, 2022 ; Lin et al, 2023 ), These dietary interventions delayed the onset of the disease, reducing or even reversing its motor and cognitive symptoms ( Guo et al, 2023 ). Lin et al found that IF may exert neuroprotective effects on MS patients through several mechanisms, including (1) regulation of blood glucose levels and enhancement of insulin sensitivity; (2) inhibition of inflammatory responses; (3) autophagy activation; and (4) reduction of oxidative stress ( Lin et al, 2023 ).…”
Section: Treatment Strategies and Future Prospectsmentioning
confidence: 99%